Stromal PTEN determines mammary epithelial response to radiotherapy - Gina M. Sizemore (Nature Portfolio, 2018)
The tumor microenvironment influences tumor progression. Here the authors show that lack of stromal PTEN phosphatase induces DNA repair defects in the neighboring mammary gland epithelial cells via hyperactivation of EGF-receptor signaling, resulting in higher radiation-induced DNA damage and hyperplasia.